Pengaruh Garam dan Enzim Transglutaminase Terhadap Sifat Fisik dan Sensori Daging Restrukturisasi Ikan Mata Goyang - Fawzya, Yusro Nuri; Gunawan, Gunawan; Patantis, Gintung (Jurnal Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
ABSTRACTThe important thing considered in the processing of fish mince meat based products is gel forming ability, which is affected by additives applied in the processing of the products. This research was aimed at studying the effect of TGase and salt addition on the physical and sensory properties of restructured product from Priacanthus macracanthus. Salt was added into minced meat at the concentration of 0, 1 and 2%, TGase with the concentration of 0; 0.3; 0.6 and 1%. The meat dough was then filled into plastic tubes and heated at 30oC for an hour before being heated at 90oC. The restructured meat was then evaluated its sensory properties texture profile (hardness,chewiness, gumminess, cohesiveness, springiness and breaking force, deformation/distance, gel strength), and its microscopic observation under the scanning electron microscope. The result showed that addition of salt as well as TGase gave significant effect on the sensory properties related to texture, appearance and brightness; and physical properties ofthe restructured products espescially gumminess and breaking force. Based on the sensory score, addition of 2% salt wasenough to produce gel which met with panelist preference, however based on the physical/texture properties addition of 2% salt and 0.3% TGase was needed to increase the gel properties. At this treatment combination, the gel strength produced was 3,235 g cm.